On some problems of the optimal stopping of stable stochastic processes - Mackevičius, V. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Мацкявичюс. О некоторых задачах оптимальной остановки устойчивых случайных процессовV. Mackevičius. Apie kai kuriuos stabilių atsitiktinių procesų optimalaus sustabdymo uždavinius